2016
DOI: 10.15265/iy-2016-047
|View full text |Cite
|
Sign up to set email alerts
|

Some Innovative Approaches for Public Health and Epidemiology Informatics

Abstract: SummaryObjectives: Summarize excellent current research published in 2015 in the field of Public Health and Epidemiology Informatics. Methods: The complete 2015 literature concerning public health and epidemiology informatics has been searched in PubMed and Web of Science, and the returned references were reviewed by the two section editors to select 14 candidate best papers. These papers were then peer-reviewed by external reviewers to allow the editorial team an enlightened selection of the best papers. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…ML models have proven to be helpful in the medical and health sciences, particularly in the areas of diagnosis and outcome prediction (27). Previous research has suggested that the application of ML models in the healthcare industry, although still in the early stages, is primarily focused on the early diagnosis of chronic diseases, predicting future disease incidence, conducting epidemiological studies, and facilitating evidence-based decision-making (27)(28)(29)(30)(31)(32). There is also evidence supporting the use of AI and ML models to predict AMR among bacterial species based on whole genome sequencing (12,13,(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…ML models have proven to be helpful in the medical and health sciences, particularly in the areas of diagnosis and outcome prediction (27). Previous research has suggested that the application of ML models in the healthcare industry, although still in the early stages, is primarily focused on the early diagnosis of chronic diseases, predicting future disease incidence, conducting epidemiological studies, and facilitating evidence-based decision-making (27)(28)(29)(30)(31)(32). There is also evidence supporting the use of AI and ML models to predict AMR among bacterial species based on whole genome sequencing (12,13,(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…An ‘other’ category had existed at that stage, which primarily referred to innovations, exemplars, government directives, etc. A combination of deductive thematic analysis, informed by the literature on harnessing information systems to improve patient care, 6574 LHS, 4,6,9,10 data privacy legislation, 75–77 and public policy, 78,79 and a more inductive iterative approach that allowed new themes to emerge from the data were used. 80 In the fifth stage, we applied this analytical framework to code further transcripts.…”
Section: Methodsmentioning
confidence: 99%
“…We applied the analytical methods used by epidemiological reference observatories in France for the general population, such as the French Syndromic Sentinel Network 10,22 or the Research Institute for the exploitation of health data (IRSAN) 23 . IRSAN has in particular utilised data from the records of the physicians of SOS Médecins since 2012.…”
Section: Methodsmentioning
confidence: 99%